Arctic summary report : outer continental shelf oil and gas activities in the Arctic and their onshore impacts - Jackson, Joanne Barnes.; Kurz, Frederick N.; Outer Continental Shelf Oil and Gas Information Program (U.S.); United States. Minerals Management Service. (Reston, Va. : Rogers, Golden & Halpern, 1983)
"January 1983." At head of title: U.S. Department of the Interior, Minerals Management Service. Includes bibliographical references. Mode of access: Internet. 17